Answer:
![g(x) = f(x - 1) + 3 = x^3 - 3x^2 + 3x + 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/v7idn8mdooy5d2sk4amu9n52ucfwzklgqu.png)
Explanation:
g(x) is f(x) moved one to the right, as well as moved 3 up (The inflection point was (0,0) on f(x), and is now at (1, 3) at g(x)).
Therefore, to move f(x) one to the right, we must subtract 1 from x, making it
, and add 3 to the y value, making it
![f(x - 1) + 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/iwqwdc9pxs5vxo4zhw0nk4xzrxkxjflq8z.png)
![g(x) = f(x - 1) + 3\\\to g(x) = (x - 1)^3 + 3\\\to g(x) = x^3 -3x^2 + 3x - 1 + 3\\\to g(x) = x^3 - 3x^2 + 3x + 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/8s4o6lyxrs8sbpy9g0n9hhmkolgtm5elvj.png)